RPSA TAKES PART IN SETTING THE NUMBER OF STATE-FUNDED PLACES FOR ADMISSION FOR THE PROGRAMS IN POLITICAL SCIENCE, WORLD REGIONAL STUDIES AND REGIONAL STUDIES OF RUSSIA IN RUSSIAN UNIVERSITIES - статья Редакционная (Сравнительная политика)
.